Circulating tumor cells in patients with recurrent or metastatic head and neck carcinoma: prognostic and predictive significance. - Salvatore Grisanti; Camillo Almici; Francesca Consoli; Michela Buglione; Rosanna Verardi; Andrea Bolzoni-Villaret; Andrea Bianchetti; Chiara Ciccarese; Monica Mangoni; Laura Ferrari; Gianpaolo Biti; Mirella Marini; et al. (PLoS ONE, 2014)
INTRODUCTION: We investigated the frequency of detection and the prognostic and predictive significance of circulating tumor cells (CTCs) in patients with recurrent/metastatic (R/M) head and neck carcinoma (HNC) before starting systemic therapy. PATIENTS AND METHODS: Using the CellSearch technology, CTCs were assessed prospectively in peripheral blood of 53 R/M-HNC patients. We performed spiking experiments to test the diagnostic performance of the CellSearch platform in identifying squamous carcinoma cells. RESULTS: CTCs were identified in 14 (26%) and 22 (41%) patients at baseline and at any time point, respectively. In univariate analysis ≥2 CTCs had a poorer prognostic role than 0-1 CTC. In multivariate analysis, the presence of one CTC or more was associated with a poor prognosis both in terms of progression-free survival (PFS) [Hazard Ratio (HR): 3.068, 95% confidence interval (CI): 1.53-6.13, p 0.002] and overall survival (OS) [HR: 3.0, 95% CI: 1.48-6.0, p 0.002]. A disease control after systemic therapy was obtained in 8% of CTC-positive patients as opposed to 45% in CTC-negative ones (p 0.03). The epidermal growth factor receptor (EGFR) expression was identified in 45% of CTC-positive patients. DISCUSSION: In conclusion, CTCs are detected in one out of three patients with RM-HNC. CTC detection is a strong prognostic parameter and may be predictive of treatment efficacy. The frequency of EGFR expression in CTCs seems to be lower than that expected in the primary tumor.